Citizens in Peace Processes. (October 2022) - Haass, Felix; Hartzell, Caroline A.; Ottmann, Martin
Citizen engagement in and support for peace processes have been deemed important for sustainable peace after civil wars. Yet much of what we know about peace processes in civil wars centers on the interests of elite actors. This special feature aims to advance a research agenda focusing on citizens in peace processes to address this mismatch. In the introduction to the special feature, we first present empirical evidence situating citizens in relation to civil war peace processes. We then trace the current state of the literature on the roles of citizens in peace processes. Following that, we introduce a conceptual framework designed to improve scholarly analysis of the political behavior of citizens in peace processes. We also locate the individual contributions to the special feature within the framework in order to demonstrate its utility and as a means of helping to identify directions for future research.